Do Successive Preterm Births Increase the Risk of Postpartum Depressive Symptoms? - Timothy O. Ihongbe; Saba W. Masho (Hindawi Limited, 2017)
Background. Postpartum depression and preterm birth (PTB) are major problems affecting women's health. PTB has been associated with increased risk of postpartum depressive symptoms (PDS). However, it is unclear if PTB in women with a prior history of PTB is associated with an incremental risk of PDS. This study aims to determine if PTB in women with a prior history of PTB is associated with an incremental risk of PDS. Methods. Data come from the 2009-2011 national Pregnancy Risk Assessment Monitoring System. Study sample included 55,681 multiparous women with singleton live births in the index delivery. Multiple logistic regression was used to examine the association between PTB and PDS. Results. The risk of PDS was 55% higher in women with PTB in both deliveries (aRR = 1.55; 95% CI = 1.28-1.88) and 74% higher in women with PTB in the index delivery only (aRR = 1.74; 95% CI = 1.49-2.05), compared to women with term deliveries. Conclusions. Preterm birth is a risk factor for PDS. PTB in women with a prior history of PTB is not associated with an incremental risk of PDS. Routine screening for PDS should be conducted for all women and closer monitoring should be done for high risk women with PTB.